Al-Qur'an Literacy Solution for students: Assistance with the Introduction of Hijaiyah Letters Based On the Tilawati Method at NU Palangka Raya Middle School - Rahman, Zaini; Hakim, M. Luqman; Yuliani, Hadma (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This community service aimed to address the low proficiency in Qur'anic reading among students at NU Palangka Raya Middle School, particularly their inability to recognize and pronounce hijaiyah letters correctly. The study focused on improving Al-Qur'an literacy by facilitating effective learning of the hijaiyah alphabet using the Tilawati method, which is essential for proper tajwid application. Method: A Participatory Action Research (PAR) approach was employed, involving five stages: problem identification, joint planning, implementation, evaluation, and follow-up. The intervention targeted Class IX students during PAI (Islamic Religious Education) lessons and utilized the Tilawati method with the